Documenting Instructional Practices in a Literacy‐Infused Arts Program: Respecting Pedagogues From the Community. Issue 1 (13th May 2013) - Brooks, Wanda; Smith, Michael W.
Abstract: This study examines the instructional practices around literacy that characterized the work of a community based arts program designed for urban adolescents. Two primary sources of data were collected: field notes on approximately 35 hours of instruction spread across seven months and interviews with the program's staff and students. Four distinct instructional episodic structures were observed: explicit instruction, collaborative or individual construction that provided time for students to engage in creative literacy and artistic activity, serial performance in which teachers are on as equal a footing as possible as students, and scaffolded practice that is informed by a belief that all can succeed can foster deep engagement in literate activity. Abstract : FREE author podcast